2022
DOI: 10.3389/fneur.2022.912923
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Brain Activity and Functional Connectivity by Acupuncture Combined With Donepezil on Mild-to-Moderate Alzheimer's Disease: A Neuroimaging Pilot Study

Abstract: BackgroundFunctional brain imaging changes have been proven as potential pathophysiological targets in early-stage AD. Current longitudinal neuroimaging studies of AD treated by acupuncture, which is one of the growingly acknowledged non-pharmacological interventions, have neither adopted comprehensive acupuncture protocols, nor explored the changes after a complete treatment duration. Thus, the mechanisms of acupuncture effects remain not fully investigated.ObjectiveThis study aimed to investigate the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Yijun Zhan recruited a total of 44 patients diagnosed with mild to moderate AD and 22 healthy subjects as controls [1] . The AD patients were randomly assigned into either the treatment group or the control group.…”
Section: Clinical Research Progress Of Acupuncture Combined With Medi...mentioning
confidence: 99%
“…Yijun Zhan recruited a total of 44 patients diagnosed with mild to moderate AD and 22 healthy subjects as controls [1] . The AD patients were randomly assigned into either the treatment group or the control group.…”
Section: Clinical Research Progress Of Acupuncture Combined With Medi...mentioning
confidence: 99%
“…The top 10 institutions with the most publications are listed in Table 2. The most productive institution was Beijing University of Chinese Medicine (36 publications), followed by Capital Medicine University (23) and Guangzhou University of Chinese Medicine ( 16). The highest average citation was Capital Medicine University (25.3) and the highest centrality (0.16), which indicated that it had a high influence and intermediary role.…”
Section: Contribution Of Institutionsmentioning
confidence: 99%
“…The top 5 keyword co-occurrences and centrality are summarized in Table 5. The top frequency of keywords was AD (61), followed by acupuncture (39), dementia (36), memory (23), and the hippocampus (23). The keyword of high centrality indicates the hotspots and turning point of this field, and its value ranges from 0 to 1.…”
Section: Keyword Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that AD is one of the most prevalent central neurodegenerative diseases [ 29 – 31 ]. Brain imaging alterations have been considered the underlying pathological targets in AD [ 32 ]. Accordingly, it would be valuable to explore the central mechanisms of acupuncture in AD.…”
Section: Introductionmentioning
confidence: 99%